2022
DOI: 10.1021/acsbiomaterials.2c00295
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-2-Responsive Surface-Changeable Liposomes Decorated by Multifunctional Peptides to Overcome the Drug Resistance of Triple-Negative Breast Cancer through Enhanced Targeting and Penetrability

Abstract: Although nanomedicine has demonstrated great potential for combating drug resistance, its suboptimal recognition of malignant cells and limited transport across multiple biological obstacles seriously impede the efficacious accumulation of drugs in tumor lesions, which strikingly limits its application in the clinical therapy of drug-resistant triple-negative breast cancer (TNBC). Hence, a surface-variable drug delivery vehicle based on the modification of liposomes with a multifunctional peptide (named EMC) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 67 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…Under the EPR effect, the nanoplatform triggered the release of the PD-1 blocker AUNP-12 in the TME via MMP-2, activated T cells, and released the oxygenase inhibitor NLG919 to achieve dual targeting. In another study about MMP-2-responsive liposome, DOX and EGFR were loaded to relieve TNBC drug resistance through drug efflux reduction (Liu et al, 2022). The highly expressed MMP-2 enzyme catalyzes the cleavage of the EGFR-targeted bullet from the carrier, and DOX was released under the action of the lysosome.…”
Section: Enzyme-responsive Nanodrug Delivery Systemsmentioning
confidence: 99%
“…Under the EPR effect, the nanoplatform triggered the release of the PD-1 blocker AUNP-12 in the TME via MMP-2, activated T cells, and released the oxygenase inhibitor NLG919 to achieve dual targeting. In another study about MMP-2-responsive liposome, DOX and EGFR were loaded to relieve TNBC drug resistance through drug efflux reduction (Liu et al, 2022). The highly expressed MMP-2 enzyme catalyzes the cleavage of the EGFR-targeted bullet from the carrier, and DOX was released under the action of the lysosome.…”
Section: Enzyme-responsive Nanodrug Delivery Systemsmentioning
confidence: 99%
“…This targeted nanocarrier provided potential therapeutics to control tumor growth in drug-resistant TNBC via EGFR targeting and also exhibited controlled release, and prevent transporter efflux which helps the drug to be bioavailable at the tumor site. This study suggested that enzyme stimuli based targeted nanoplatform has the potential to treat drug-resistant TNBC and also enhanced the penetration of drug into the TME [ 226 ].…”
Section: Stimuli Based Targeting Approaches In Nano Drug Delivery Sys...mentioning
confidence: 99%
“…The liposome specically targeted cancer cells and showed high therapeutic potential. 101 The bombesin/gastrin-releasing peptides (BN/GRP) stimulate cancer progression through interaction with GPCRs. Peptide antagonists binding the GRP receptors inhibit cancer growth in various cancers 98 (Fig.…”
Section: Acps Which Alter Tumor Growth and Block Metastasismentioning
confidence: 99%